Evaluation of Urban Waterfront Redevelopment Process in Banjarmasin City, South Kalimantan Province, Indonesia - Rifky, Andini Amalia; Supriyono, Bambang; Wanto, Alfi Haris; Kawano, Motoko (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2017)
Waterfront project toward urban redevelopment has become common in many countries, including Indonesia. Based on the field survey and documents research in Banjarmasin, during 2016 to 2017, this study aims to evaluate the urban waterfront redevelopment. This study revealed that there are three phases of Banjarmasin waterfront redevelopment process, namely river normalization, creating a new economy, and rediscovering identity. Findings suggested that Banjarmasin government has attained success in both the physical development and the maintenance of the traditional river culture as Banjarmasin’s image. Another finding also suggested that decentralization has a part to play in the Banjarmasin waterfront process, because Banjarmasin government gives more attention on waterfront projects, by allocating a huge budget for this purpose.